PRIMA-1MET Inhibits Growth of Mouse Tumors Carrying Mutant p53 - Nicole Zache; Jeremy M. R. Lambert; Klas G. Wiman; Vladimir J. N. Bykov (Cellular Oncology)
Reactivation of the tumor suppressor activity to mutant p53 should trigger massive apoptosis and eliminate tumors. The low molecular weight compounds PRIMA-1 and the structural analog PRIMA-1MET reactivate human mutant p53 in vitro and suppress growth of human tumor xenografts in SCID mice. However, little is known about their effect on mouse mutant p53 in mouse tumor cells. We have examined the effect of PRIMA-1MET on mouse sarcomas, mammary carcinomas and chemically induced fibrosarcomas. PRIMA-1MET showed potent growth suppression in mutant p53-carrying mouse tumors in vitro and a significant anti-tumor effect in syngeneic mice in vivo. These results demonstrate that PRIMA-1MET targets mouse tumors carrying mutant p53 and provide strong support for the anti-tumor efficiency of PRIMA-1METin vivo.